Pengaruh Internet Marketing terhadap Brand dan Kinerja pada Universitas Swasta di Jakarta Barat - Kurniali, Sartika (Bina Nusantara University, 2012)
Several purposes of this research writing are to comprehend marketing activity at a private university in West Jakarta, the relationship between internet marketing with the brand, the relationship between internet marketing and performance of private universities in West Jakarta, and the relationship between the brand and the university's performance in West Jakarta. Data are taken from questionnaires to the management of the private university in West Jakarta and were analyzed using descriptive analysis as well as statistical analysis for non-parametric Spearman correlation. The results revealed that there was no significant relationship between neither internet marketing and brand nor internet marketing and performance. However, the internet marketing sub-variables, which proved to have a significant effect on brand or performance, is communication. Meanwhile, brand has a significant effect on performance. It canbe concluded that the internet marketing activities performed by the university’s management does not have a high impact to brand and performance eventhough it has a positive correlation. Therefore, it is necessary to improve the communication component and to make improvement especially on other four components (product, price, community, and distribution) which currently have not provided any significant influence.